Planning Kerala's Irrigation Projects Technological Prejudice and Politics of Hope - V Santhakumar R Rajagopalan S Ambirajan (Economic and Political Weekly March 25, 1995, 1995)
The political objective of achieving self-sufficiency in rice production in Kerala supported the planning of major irrigation projects in alt the river basins of Kerala. The irrigation engineers who planned these projects showed a technological prejudice as they rarely sought alternative methods and scales of irrigation in each of these basins. This prejudice is of serious concern in a high rainfall area like Kerala, where the dam and canal-based system is 'naturally' costly and where there is a possibility of meeting the relatively small requirement of additional water through less expensive means. The objective of achieving self-sufficiency in rice and the policy of having major irrigation projects in all the basins seem to be based on the neglect of the specific agro-climatological and agro-ecological features of humid-tropic Kerala